A-72 Neuropsychological Functioning in Primary Dystonia: A Multi-Domain Meta-Analysis. (30th August 2021) - Aita, Stephen; Del Bene, Victor A; Pizer, Jasmin H; Hawley, Nanako A; Niccolai, Lindsay; Marotta, Dario A; Walker, Harrison C; Gerstenecker, Adam; Martin, Roy C; Clay, Olivio J; Crowe, Michael; Triebel, Kristen L; et al.
Abstract: Objective: Primary dystonia is conventionally seen as a motor disorder, though growing literature indicates cognitive dysfunction among persons with primary dystonia (PWD). Here, we completed a meta-analysis comparing cognition on clinical measures between PWD and normal controls. Method: We searched PubMed, Embase, Cochrane Library, Scopus, and PsycINFO using a uniform search-strategy to locate original research comparing cognition between PWD and control samples. All analyses were modeled under random-effects. We used Hedge's g as a bias-corrected estimate of effect size. Between-study heterogeneity was assessed using Cochran's Q and I2. Results: The initial search strategy yielded 866 results. Twenty studies were analyzed (PWD n = 739, control n = 865; 254 effect sizes extracted). Meta-analysis showed a significant combined effect size of primary dystonia across all studies (g = −0.55, p < 0.001), with low heterogeneity (Q = 23.60, p = 0.21, I2 = 19.49). Trim-and-fill procedure estimated 6 studies missing due to publication bias (adjusted g = −0.47, Q = 44.58). Within-domain effects of primary dystonia were: Motor/Non-Motor Speed = −0.76, Global Cognition/Orientation = −0.65, Language = −0.62, Executive Functioning = −0.50, Learning/Memory = −0.46, Visuospatial/Construction = −0.44, and Simple/Complex Attention = −0.36. Heterogeneity was generally low within domains. Effects were comparable between Speed tasks with (g = −0.85) and without (g = −0.80) a motor component. Meta-regressions indicated age, education, gender, and disease duration were not related to effect sizes. Conclusions: PWD consistently demonstrated lower performances on neuropsychological tests compared to controls. Effect sizes were generally moderate in strength, with smallest effects in Simple/Complex Attention, and largest in Motor/Non-Motor Speed. Within the Speed domain, results suggested cognitive slowing beyond effects from motor symptoms. This quantitative summary indicates that PWD experience difficulties in multiple aspects of cognition, as detected by neuropsychological tests.